Microstructure of tooth pastes for the treatment of hypersensitivity of teeth - Коленко, Ю. Г.; Мялківський, К. О. (Actual Dentistry, 2019)
Actuality. The prevalence of hypersensitive of hard tissue teeth varies from 64 to 92 %, depending on gender and age. It is one of the first signs of the pathology of periodontal tissues, which can occur on the background of clinically unaffected tissues. The aim: to study the micro-composition and microstructure of toothpastes for the treatment of hypersensitivity of hard dental tissues in case of periodontal tissue pathology. Materials and methods of research. For carrying out scanning electron-microscopic research we selected two pastes for the treatment of hypersensitivity of hard tissues of teeth declared by the manufacturer. Results: the analysis showed that the particle size of the Lacalut Extra Sensitive toothpaste is less than 1 micron, they have a rounded smooth surface. Lacalut Extra Sensitive largely contains desensitizing agents, such as aluminum, potassium, and fluorine compounds. A sufficiently significant amount of silicon compounds gives the paste abrasiveness, which allows you to remove dental plaques and at the same time not to injure the surface of the tooth enamel. Electron microscopic examination of the Sensodyne fast action toothpaste showed that the particle size is less than 1 micron, but single particles of 2.5 micron are present. X-ray analysis of the toothpaste «Sensodyne quick action» found a significant amount of silicon and strontium in the toothpaste, a small amount of potassium was also determined. Conclusion. The analysis shows the presence of components in selected toothpastes, which facilitate the removal of dental deposits, provide dessenitazernye properties of pastes, which makes them quite effective for reducing the increased sensitivity of hard tooth tissues. Key words: hypersensitivity of hard tooth tissues, toothpaste, Lacalut Extra Sensitive, «Sensodyne quick action».